Tensions and Learnings in Teacher Training: Teaching Recent History in Memory Sites (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
This paper explores how prospective History teachers connected memory sites, the teaching of recent history, and citizenship education through a visit to the former Clandestine Detention Center Comisaría 4ª in Santa Fe. The activity, guided by the institution’s staff and including secondary school students, sought to promote reflection on pedagogical practices. University students completed assignments, engaged with bibliography, documented activities, and observed adolescents’ interactions. They also identified emotional and conceptual tensions generated by the experience. The study examines students’ perspectives on dilemmas such as duty of memory versus plurality of memories and ethical-political commitment versus historical reconstruction. Follow-up interviews offered deeper insights into how future teachers articulate past, present, and future, and how they envision the role of memory in democratic construction.
Keywords: teacher education; history teaching; space; memory